Trixie and the razzle-dazzle ruse - Berrow, G. M. (My little pony (Little, Brown and Company), 2017)
When Trixie looks for an uncommon cloak for her greatest show ever in Ponyville, a mishap gives her the capacity to transform standard things into valuable gems just by touching them, which turns out to be more trouble than it is worth.